Profitabilitas dan Kebijakan Dividen Perusahaan Manufaktur Indonesia dengan Pemoderasi Ukuran Perusahaan - Riska Agustin; Nur Islamia (Jurnal Visi Manajemen, 2024)
Abstract: Analysis of the company's financial ratios is needed by investors to choose a company that will be used as a place to invest. The financial ratio that can be used to assess the company is the profitability ratio measured by Return on Asset (ROA). If the profitability of a company is high in terms of stock returns, then investors tend to choose the company as a place to invest their shares. In addition to profitability, company size is also a consideration for investors in investing, companies with a larger size indicate that the company is superior in profit and performance. This research uses quantitative methods with a sample of 21 companies using purposive sampling method. The results show that profitability in manufacturing companies has no effect on dividend policy, while the size of manufacturing companies affects dividend policy. The results of moderation testing show that company size does not moderate the effect of profitability of manufacturing companies on dividend policy to be distributed to shareholders. Companies are expected to have an appropriate strategy because dividend policy considerations are closely related to financial capabilities, business projections, and economic expectations of shareholders to invest.